2023
DOI: 10.1098/rsos.221225
|View full text |Cite
|
Sign up to set email alerts
|

Social disappointment and partner presence affect long-tailed macaque refusal behaviour in an ‘inequity aversion’ experiment

Abstract: Protest in response to unequal reward distribution is thought to have played a central role in the evolution of human cooperation. Some animals refuse food and become demotivated when rewarded more poorly than a conspecific, and this has been taken as evidence that non-human animals, like humans, protest in the face of inequity. An alternative explanation—social disappointment—shifts the cause of this discontent away from the unequal reward, to the human experimenter who could—but elects not to—treat the subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…However, these findings have mainly been obtained in nonsocial settings. Considering previous results of the experiment of Titchener et al (2023), which was conducted with the same study population as the current study, we expected our long-tailed macaques to react differently towards a human food distributor (an experimenter) compared to a machine distributor (an automated food dispenser). We expected to find a general tendency towards risk-seeking, in accordance with the classification of this species.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, these findings have mainly been obtained in nonsocial settings. Considering previous results of the experiment of Titchener et al (2023), which was conducted with the same study population as the current study, we expected our long-tailed macaques to react differently towards a human food distributor (an experimenter) compared to a machine distributor (an automated food dispenser). We expected to find a general tendency towards risk-seeking, in accordance with the classification of this species.…”
Section: Introductionmentioning
confidence: 98%
“…But depending on the experimental protocol, previous test experience, and the relationship with the experimenter, nonhuman subjects could just as well expect a human experimenter to reward them according to a different rationale, for example, to pick the better of two options. Indeed, recent research has shown that nonhuman primates seem to hold certain expectations towards their human experimenters: for example, two recent studies (Engelmann & Herrmann, 2016;Titchener et al, 2023) showed that chimpanzees and long-tailed macaques refused to participate in an experimental task more often when a human experimenter rewarded them with less desirable food compared to a conspecific; this effect was absent when a machine distributed the rewards. In another study (Stevens et al, 2011), bonobos distinguished human experimenters according to their reliability in providing food: subjects were less willing to wait for delayed rewards when confronted with a previously unreliable experimenter compared to a reliable experimenter.…”
Section: Introductionmentioning
confidence: 99%
“…This response, commonly referred to as inequity aversion and considered to reflect social comparison of payoffs, has attracted considerable attention due to its putative involvement in the evolution of a sense of fairness and the stabilization of cooperation 1 , 3 6 . However, skepticism and controversy persist over reports of inequity aversion in non-human animals, particularly primates, due to a variety of proposed alternative explanations for observed responses 7 13 (but see also Brosnan 14 and van Wolkenten et al 15 ), as well as numerous failed replications across research groups 16 21 (but see also Brosnan et al 22 , Hopper et al 23 , and Fletcher 24 ; see McGetrick and Range 7 for a review).…”
Section: Introductionmentioning
confidence: 99%